1) 2Cr + 3O2 = 2Cr2O3
Cr2O3 + 6HCl = 2CrCl3 + 3H2O
CrCl3 + 3NaOH = 3NaCl + Cr(OH)3↓
Cr(OH)3 + H3PO4 = CrPO4 + 3H2O
2) 2Sr + O2 = 2SrO
SrO + H2O = Sr(OH)2
3Sr(OH)2 + 2H3PO4 = Sr3(PO4)2 + 6H2O
3) 4Al + 3O2 = 2Al2O3
Al2O3 + 3H2SO4 = Al2(SO4)3 + 3H2O
Al2(SO4)3 + 6NaOH = 2Al(OH)3↓ + 3Na2SO4
2Al(OH)3 + 3CO2 = Al2(CO3)3 + 3H2O
Al2(CO3)3 = Al2O3 + 3CO2↑
1) 2Cr + 3O2 = 2Cr2O3
Cr2O3 + 6HCl = 2CrCl3 + 3H2O
CrCl3 + 3NaOH = 3NaCl + Cr(OH)3↓
Cr(OH)3 + H3PO4 = CrPO4 + 3H2O
2) 2Sr + O2 = 2SrO
SrO + H2O = Sr(OH)2
3Sr(OH)2 + 2H3PO4 = Sr3(PO4)2 + 6H2O
3) 4Al + 3O2 = 2Al2O3
Al2O3 + 3H2SO4 = Al2(SO4)3 + 3H2O
Al2(SO4)3 + 6NaOH = 2Al(OH)3↓ + 3Na2SO4
2Al(OH)3 + 3CO2 = Al2(CO3)3 + 3H2O
Al2(CO3)3 = Al2O3 + 3CO2↑